Trade policy and Green Growth - Evi Susanti Tasri (Universitas Andalas, 2017)
Nowadays, Limited Natural resources and population Growth demanded a fundamental change in economic policy. This paper tried to assess the link between economic growth especially green growth and Trade policy in the form of economic openness. The Study conducted by using survey literature and empiric. The outcomes of theoretical study of literature and empirical finding using panel data showed a significant effect of openness trade policy on Green GDP growth of countries.